The role of stress factors in severity of Cytospora plurivora in greenhouse and field plantings of 13 peach (Prunus persica) cultivars - Miller, Stephan T.; Wright, Sean; Stewart, Jane E. (Frontiers in Plant Science, 2023)
Understanding the host-pathogen-environmental interactions in a pathosystem is essential for management of diseases and diminished crop yields. Abiotic stressors such as cold damage, water deficit, and high pH soils can be major limiting factors to tree fruit production. Along with decreased yields, these abiotic factors have direct implications for disease severity within orchards. Cytospora plurivora is a ubiquitous fungal canker pathogen in western Colorado and is a major focus in integrated pest management strategies due to the pathogen's necrotrophic lifestyle. This research evaluated the influence of biotic and abiotic stress factors on peach tree health. Thirteen peach cultivars were placed under abiotic stress and inoculated with C. plurivora in greenhouse and field conditions. Under deficit-irrigation, C. plurivora infections were significantly larger and more severe in both greenhouse and in field trials when compared to the full-irrigation controls. In controlled greenhouse conditions, a positive correlation between lesion size and water potential was evident, but no trend of cultivar tolerance was observed. Further, increase of irrigation water pH, through additions of sodium carbonate and bicarbonate, in greenhouse trials resulted in decreased leaf water potentials and increased pathogen necrotic tissue volumes (mm 3 ). In field trials, there was no positive relationship between lesion size and water potential; trees with the most negative water potentials had the smallest lesions sizes that didn't correspond to cultivar suggesting that other abiotic or biotic factors may be shielding water stressed trees from increased pathogen aggression. This research highlights the importance of proper irrigation and soil pH management as tools for the management of Cytospora canker in peach orchards.INTRODUCTION Management of abiotic stressors, such as water deficit, high pH, and cold damage, is vital for agricultural crop success. Abiotic stressors are considered the primary limiting factors of agricultural production, affecting 70% of agricultural crops around the world, especially when stressors occur simultaneously (